1989
DOI: 10.1084/jem.170.6.2011
|View full text |Cite
|
Sign up to set email alerts
|

The staphylococcal toxic shock syndrome toxin 1 triggers B cell proliferation and differentiation via major histocompatibility complex-unrestricted cognate T/B cell interaction.

Abstract: Toxic shock syndrome toxin 1 (TSST1)t is a 22-kD exotoxin produced by most strains of Staphylococcus aureus isolated from patients with toxic shock syndrome (TSS) (1) . TSST 1 is a potent activator of monocytes and T cells . It acts on monocytes to induce the synthesis of IL-1 and TNF (2-4) . TSSTl also triggers T cell activation and proliferation (5), as well as the production of large amounts of various lymphokines such as IL-2 (6) and IFN-y (7) . The massive induction of monokine and lymphokine production b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 30 publications
9
39
0
Order By: Relevance
“…The studies reported here support this hypothesis. While this manuscript was in preparation, Mourad et al reported similar results using the Staphylococcal toxic shock syndrome toxin (13). Together, these two reports suggest that productive Th-B cell bridging may be a common feature of microbial superantigens .…”
Section: Methodssupporting
confidence: 57%
“…The studies reported here support this hypothesis. While this manuscript was in preparation, Mourad et al reported similar results using the Staphylococcal toxic shock syndrome toxin (13). Together, these two reports suggest that productive Th-B cell bridging may be a common feature of microbial superantigens .…”
Section: Methodssupporting
confidence: 57%
“…Although at least 11 enterotoxins have been identified, it is widely believed that more remain to be discovered, since the known enterotoxin genes do not account for all cases of food poisoning and toxic shock syndrome. Some of the exotoxins are also superantigens, and it has been suggested that they may even play a role in autoimmune diseases (8,18). For instance, the enterotoxins have been suspected of triggering symptoms resembling arthritis in patients with staphylococcal toxic shock syndrome (6,16).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the superantigen binding may, to some extent, substitute for the cognate T helper-B cell interaction signal and ready B cells that have interacted with antigen to respond more efficiently to lymphokines. In this regard, superantigen binding to class I1 MHC molecules on monocytes results in interleukin-1 and interleukin-6 release (72,90), while Mourad et al report that TSST binding to class I1 MHC molecules on resting human B cells enhances their proliferative response to B cell growth factors (82).…”
Section: Microbial Superantigens As Mediators Of Gvh-like Diseasementioning
confidence: 99%
“…To approach this question, high-density (resting) tonsillar B cells were isolated on discontinuous Percoll density gradients, incubated with final medium or MAM for 1 hour at 37"C, and washed extensively. B cell populations preincubated with medium alone or with MAM were cultured with MAM-specific T helper cells and assayed for T cell-dependent B cell activation by the cell surface expression of CD23, an early B cell activation antigen (85), and for polyclonal Ig secretion, determined by (82). Thus, at least 2 distinct microbial superantigens bind to class 11 MHC antigens on the surface of resting human B cells and effectively activate autologous superantigen-reactive T helper cells, which in turn trigger polyclonal immunoglobulin production by the superantigen-bearing B cell population.…”
Section: Microbial Superantigens As Mediators Of Gvh-like Diseasementioning
confidence: 99%